Investigating the Factors of Green Purchase Intention on Green Cosmetics in Indonesia - Widiantari, Nindiana; Rachmawati, Indira (Riviera Publishing, 2023)
Research aims to investigate the factors influencing the intention to purchase green cosmetics in Indonesia. The applied research method is quantitative and causal, utilizing a non-probability sampling technique with 300 respondents. Structural Equation Model (SEM) with Partial Least Squares (PLS) is employed as the data analysis tool. The study's findings indicate that the perception of behavioral control, epistemic value, and emotional value does not significantly influence the intention to purchase environmentally friendly cosmetic products in Indonesia. On the other hand, health awareness and environmental knowledge play a crucial role in shaping environmental attitudes. Subjective norms, environmental attitudes, functional price value, social value, and conditional value significantly impact the intention to purchase environmentally friendly cosmetic products. The implications of these findings offer insights to the cosmetics industry to align their marketing strategies with values that are more socially and environmentally oriented, aiming to enhance consumer intention to purchase green cosmetics in Indonesia.